Differences in Learning Outcomes by Using Educational Video Media and Documentary Video Media in History Learning at SMA N 12 Semarang - Erniasih, Umi; Pramono, Suwito Eko; Atno, Atno (Universitas Negeri Semarang, 2021)
The purpose of this study is to find out the learning outcomes of students using video education media in history learning in X IPS Class N 12 Semarang High School in the academic year 2017/2018, to find out the learning outcomes of students using documentary video media in history learning in X IPS class SMA N 12 Semarang in the academic year 2017/2018, and to find out the differences in learning outcomes by using educational video media with documentary video media on history learning in Class X IPS SMA N 12 Semarang academic year 2017/2018. This study uses a quantitative approach to the type of experiment—research location at SMA N 12 Semarang. The instruments used in this study are documentation, tests, observations, and questionnaires. The results showed that the average learning outcome of students using educational video media was 85.5. While the average learning outcome of students using video documentary media is 74.6. In addition, through the t-test, it was produced that there were differences in the average learning outcomes between students who used educational video media and those who used documentary video media, 3,583.